Decarbonated eclogite in the mantle sources of the Wajilitag mafic-ultramafic intrusion, Permian Tarim Large Igneous Province, NW China: Evidence from Zn isotopes - Jin, Shengkai; Wang, Zhenchao; Li, Hengxu; Liu, Linghan (Journal of Asian earth sciences, 2025)
•High δ66Zn of subalkaline mafic–ultramafic intrusions was caused by decarbonation reactions between co-existing silicate and carbonates during subduction.•Decarbonation reactions are crucial for recycled carbonates in deep carbon cycling.•Accumulation of Fe-Ti oxides and olivine can lead to Zn isotopic variation in mafic–ultramafic intrusions. The formation of the Tarim Large Igneous Province (TLIP) has been linked to oceanic crust subduction, yet the specific interactions between the subducting crust and the TLIP mantle source remain ambiguous. Zn isotopes, a newly developed stable isotope system, offer promising potential for identifying recycled carbonates within the mantle. Here, a detailed analysis of Zn isotopes in the Wajilitag Fe-Ti oxide-bearing mafic–ultramafic intrusion of the TLIP is presented. The observed δ66Zn values (0.27 ‰ ± 0.03 ‰ to 0.48 ‰ ± 0.02 ‰) are heavier than those found in Mid-Ocean Ridge Basalts (MORBs; 0.24 ‰ to 0.31 ‰), potentially indicating the influence of the incorporation of recycled sedimentary carbonates into the mantle source. However, the subalkaline nature and depleted 87Sr/86Sr compositions of the Wajilitag mafic–ultramafic intrusion suggest that sedimentary carbonate incorporation into the mantle occurs via decarbonation. During these processes, Zn from the carbonates (dolomite and magnesite) is transferred to silicates (diopside and enstatite) with accompanying isotope exchange, resulting in the residual silicates inheriting and preserving the heavy Zn isotope signatures. Together with detailed petrographic observations, Rhyolite-MELTS simulations and MATLAB lsqr () function for quaternary mixing calculations, it is concluded that, variations in Zn isotopes among the intrusion lithofacies are primarily driven by differing degrees of Fe-Ti oxides and olivine accumulation. Additionally, our study highlights the potential role of recycled sedimentary carbonates in deep carbon cycling through decarbonation reactions.